Developed high gain microstrip antenna like microphone structure for 5G application - H. Yon; N. H. Abd Rahman; M. A. Aris; Hadi Jumaat (Institute of Advanced Engineering and Science, 2020)
We present a new development of microstrip antenna structure combining a simple circular structure with a ring antenna structure as the parasitic element to improve the antenna gain and bandwidth for 5G mobile application. The proposed antenna was fed by a 50Ω microstrip feeding line due to its advantages in performance. The antenna was designed and simulated using a single substrate with double layered copper (top and bottom) with the radiating patch on the top layer and full ground on the bottom layer of the same substrate. Three antennas have been designed namely; design1, design2 and design3 to complete the research works.The antennas ware simulated and optimized at 18 GHz using Computer Simulation Technology (CST) with permittivity, r = 2.2 and thickness, h = 1.57mm on low-loss material Roger RT-Duroid 5880 substrate. The antennas ware reasonably well matched at their corresponding frequency of operations. The simulation and measurement results have shown that the antenna works well. The simulation results have shown that the three antennas works well at the selected frequency. The final simulated antenna for design1, design2 and design3 has been fabricated to measure the performance and also to validate the simulation result with the measurement result. The measurement data for antenna design1, design2 and design3 shows frequency shift of 3% from the simulation result. The final protype of design3 gives 6.6dB gain, -14.51dB return loss, 180MHz bandwidth, and antenna efficiency of 53.9%. All three antennas ware measured using Vector network analyzer (VNA) and Anechoic chamber.